Platform, position, and purpose: Analyzing the studio recordings and live performances of U2 - Smith, Matthew (University of Ottawa (Canada), 2005)
This thesis explores the music of rock band U2, utilizing two perspectives: current research in popular musicology, specifically the work of Albin Zak, Allan Moore, and Lori Burns, and the thoughts of the band members of U2. These two perspectives provide the framework for the discussion that covers several examples from across the bands discography (1980-2000). The role of music in communicating with the listener is discussed from the perspective of the band members of U2. This discussion highlights the desire of the band members to actively participate in the songs' meaning by shaping the musical performance to the themes and ideas discussed within the text. The way that the text shapes the understanding is examined through a discussion of the songs "All Along the Watchtower," and "Playboy Mansion." The bands live performances are also considered, through a discussion of the Elevation Tour. The songs "Sunday Bloody Sunday," and "Bullet the Blue Sky" are discussed in-depth, taking into account the music, text, and performance from their initial studio recordings in the 1980s, to the recent performances in the Elevation Tour. The focus centers on the messages communicated through the bands music, the choices made in shaping their sound, and the importance of the details in fully understanding each performance.
Keywords: Music.